Effect of mindfulness-based stress reduction on stress levels among first-trimester pregnant women in Neglasari Public Health Center working area - Devi Khusnul Khotimah; Osep Yasier Almunsiri; Lailatul Fadilah; Alif Nurul Rosyidah (JOURNAL OF Mental Health Concerns, 2026)
Background: Pregnancy is a significant period that brings many changes, both physically and emotionally, as well as psychosocially. This condition often leads to excessive stress in pregnant women. If not addressed, it can impact the health of both the mother and the fetus. One method considered effective for managing stress is Mindfulness-Based Stress Reduction (MBSR). Purpose: To determine the effect of MBSR intervention on stress levels in pregnant women. Method: A Quasi-Experiment with a One-Group Pre- and Post-Test design. The sampling technique used total sampling with 26 respondents. The instrument used to measure stress levels was the DASS questionnaire. Results: Data analysis showed that the average stress level before MBSR intervention was 19.77, which decreased to 16.15 after the intervention, with a standard deviation of 0.710 for pre-test and 1.953 for post-test. Statistical test results showed a P-Value of 0.000 (<0.05), indicating a significant difference in stress levels before and after the intervention. Conclusion: The MBSR intervention significantly affects the reduction of stress levels in pregnant women, as evidenced by the decrease in the average stress scores before and after the intervention. Keywords: MBSR; Mindfulness; Stress; Pregnant Women.